The conquest of the soul : confession, discipline, and public order in Counter-Reformation Milan - Boer, Wietse de (Studies in medieval and Reformation thought, 2001)
Carlo and Federico Borromeo achieved fame by turning Milan into the foremost laboratory of the Italian Counter-Reformation. This monograph interprets their programme of penitential discipline as a quest to reshape Lombard society by reaching into the souls of its inhabitants.